First insight into the somatic mutation burden of neurofibromatosis type 2-associated grade I and grade II meningiomas: a case report comprehensive genomic study of two cranial meningiomas with vastly different clinical presentation. Issue 1 (December 2017) - Dewan, Ramita; Pemov, Alexander; Dutra, Amalia; Pak, Evgenia; Edwards, Nancy; Ray-Chaudhury, Abhik; Hansen, Nancy; Chandrasekharappa, Settara; Mullikin, James; Asthagiri, Ashok; Heiss, John; Stewart, Douglas; et al.
Abstract Background Neurofibromatosis type 2 (NF2) is a rare autosomal dominant nervous system tumor predisposition disorder caused by constitutive inactivation of one of the two copies ofNF2 . Meningiomas affect about one half of NF2 patients, and are associated with a higher disease burden. Currently, the somatic mutation landscape in NF2-associated meningiomas remains largely unexamined. Case presentation Here, we present an in-depth genomic study of benign and atypical meningiomas, both from a single NF2 patient. While the grade I tumor was asymptomatic, the grade II tumor exhibited an unusually high growth rate: expanding to 335 times its initial volume within one year. The genomes of both tumors were examined by whole-exome sequencing (WES) complemented with spectral karyotyping (SKY) and SNP-array copy-number analyses. To better understand the clonal composition of the atypical meningioma, the tumor was divided in four sections and each section was investigated independently. Both tumors had second copy inactivation ofNF2, confirming the central role of the gene in meningioma formation. The genome of the benign tumor closely resembled that of a normal diploid cell and had only one other deleterious mutation (EPHB3 ). In contrast, the chromosomal architecture of the grade II tumor was highly re-arranged, yet uniform among all analyzed fragments, implying that this large and fast growing tumor was composed of relatively few clones. Besides multiple gains and losses, the grade II meningioma harbored numerous chromosomal translocations. WES analysis of the atypical tumor identified deleterious mutations in two genes:ADAMTSL3 andCAPN5 in all fragments, indicating that the mutations were present in the cell undergoing fast clonal expansion Conclusions This is the first WES study of NF2-associated meningiomas. Besides secondNF2 copy inactivation, we found low somatic burden in both tumors and high level of genomic instability in the atypical meningioma. Genomic instability resulting in altered gene dosage and compromised structural integrity of multiple genes may be the primary reason of the high growth rate for the grade II tumor. Further study ofADAMTSL3 andCAPN5 may lead to elucidation of their molecular implications in meningioma pathogenesis.